Analisis Takhrij dan Pemahaman Hadis Tentang Mahar Yang Ringan - Permata, Maulin; Damanik, Nurliana; Munandar, Munandar (Jayapangus Press, 2025)
The dowry in marriage is often considered a symbol of social status, which makes its value tend to be high and burdensome for the prospective groom. However, Islam emphasizes simplicity in dowry, as stated in the hadith that the best dowry is the one that is the lightest. This hadith is often used as a reference to encourage ease in marriage, yet its implementation is still influenced by cultural traditions and social pressures. Therefore, this study aims to examine this hadith using the takhrij al-hadith method to determine the authenticity of its chain of transmission (sanad) and text (matn), as well as to understand its relevance in social and Islamic legal contexts. This research employs a qualitative approach with the takhrij technique, which includes tracing the original names, life span until death, names of students and teachers, as well as scholars' opinions regarding their credibility. The study involves tracking the hadith’s transmission in Kutub Arba‘ata ‘Asyar, along with books of Tarājim wa al-Ṭabaqāt, al-Takhrij wa al-Aṭraf, hadith commentaries, and other supporting literature. The findings indicate that the hadith in al-Mustadrak by al-Hakim al-Naisaburi holds a sahih status according to Imam Muslim’s criteria, making it a valid source of Islamic jurisprudence (hujjah). Scholars such as Shaykh al-Munawi, Shaykh al-Maghribi, Shaykh Abdurrahman bin Qasim, and Shaykh al-‘Uthaymeen interpret that the wisdom behind the simplicity of dowry is to facilitate marriage, strengthen the marital relationship, and avoid financial burdens that may hinder marriage. The conclusion of this study affirms that the principle of dowry simplicity aligns with the Islamic values of ease and contributes to marital stability. A more contextual understanding of this hadith is expected to help reduce burdensome social practices and provide a more inclusive perspective within Islamic marital law.